2015
DOI: 10.11648/j.ijnfs.20150401.13
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration and Evaluation of Produced Hamburger with Meat of Old Sheep and Pig with Added of Chia Seed (Salvia hispanica)

Abstract: Abstract:The objective of this study was to develop some hamburger meat product aimed at harnessing meat of old sheep, of little acceptance in nature, with pork and chia seed. The better acceptance formulation was used to prepare three formulations the relationship being of sheep/pork of 50/50 (w/w) and chia seed concentrations of 0%, 2% and 4%. The results showed significant difference (p ˂ 0.05) acceptability among FA formulations (without chia seed) and FC (4% chia seed) at 120 days and between FC formulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…Therefore, it had the highest protein content among all samples. A similar study was reported by Machado [23] on the decreasing protein content when chia seed was added into pig and sheep hamburger. Therefore, it was acceptable that the low chicken meat percentages indicated the low protein content in samples with chia seed powder substitution.…”
Section: Chemical Compositionsupporting
confidence: 83%
See 2 more Smart Citations
“…Therefore, it had the highest protein content among all samples. A similar study was reported by Machado [23] on the decreasing protein content when chia seed was added into pig and sheep hamburger. Therefore, it was acceptable that the low chicken meat percentages indicated the low protein content in samples with chia seed powder substitution.…”
Section: Chemical Compositionsupporting
confidence: 83%
“…Fibre is categorized as a polysaccharide, and in chia seed, lignin is the predominant insoluble fibre [26]. The same results were reported in [23] that the polysaccharides were found between 90-94%, composed with lignin, cellulose, and hemicellulose.…”
Section: Chemical Compositionsupporting
confidence: 74%
See 1 more Smart Citation